The Analysis of the Roasting Tradition (Se’i/Nu), Maternal Hemoglobin Level and the Uterine Involution Process among Puerperal Women - Korbaffo Anita Restu; Novita Ana Anggraini; Nur Yeny Hidajaturrokmah (Jurnal Ners, 2020)
Se'i/nu is one of the traditions of the local community on the island of Timor. The research objective was to prove the relationship between the roasting tradition (se'i/nu) with the hemoglobin level and the process of uterine involution in postpartum women. The research design was analytical with an observational approach. The sample consisted of 42 respondents obtained through total sampling. The independent variable was the roasting tradition (se’i/nu) and the dependent variables were hemoglobin level and maternal uterine involution. The method used to measure the roasting tradition (se’i/nu) was an observation sheet. To measure the hemoglobin level, we used a laboratory check and to measure uterine involution, we conducted a physical examination and used an observation sheet. The results showed that the largest percentage of hemoglobin levels in postpartum mothers was among those that did the roasting tradition (se'i/nu) with an abnormal hemoglobin level of 66.66% (22 people). The puerperal women who did the tradition of roasting (se'i/nu) obtained high uterine fundus and the abnormal mothers made up the largest percentage of 69.70% (23 people). There was a correlation between the roasting tradition (se'i/nu) and maternal hemoglobin level (p=0.025) and there was also a correlation between the roasting tradition (se'i/ nu) with the process of maternal uterine involution (0.00). The conclusion is that there is a prolonged uterine involution process and that the low hemoglobin levels in the puerperium may be due to exposure to chemical susceptibility as a result of inhaling polluted air due to the se'i/nu process.